2019
DOI: 10.1016/j.fertnstert.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Assisted conception does not increase the risk for mother-to-child transmission of hepatitis B virus, compared with natural conception: a prospective cohort study

Abstract: Objective: To determine whether assisted conception increases the risk for mother-to-child transmission of hepatitis B virus (HBV) infection compared with natural conception. Design: Prospective cohort study. Setting: Research laboratory. Patient(s): A total of 305 children, 176 born with assisted conception and 129 born with natural conception, were born to a total of 251 hepatitis B surface antigen-(HBsAg-) positive women. Intervention(s): None. Main Outcome Measure(s): The seropositive rates of HBsAg in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…One study on 12 babies born to couples with HBV-positive oocytes and/or embryos found that the presence of HBsAg in oocytes and embryos might not result in the vertical transmission of HBV in the offspring of chronic HBV-infected mothers [279]. A study on 251 HBsAg-positive females (305 children, 176 born with assisted conception, and 129 born with natural conception; 7.5% of children were HBsAg positive at birth), found that HBsAg positivity rate among children at birth was similar in the assisted conception group and the natural conception group (6.3% vs. 9.3%) [280].…”
Section: Effect Of Female Chronic Hbv Infection On Pregnancy Outcomes...mentioning
confidence: 99%
“…One study on 12 babies born to couples with HBV-positive oocytes and/or embryos found that the presence of HBsAg in oocytes and embryos might not result in the vertical transmission of HBV in the offspring of chronic HBV-infected mothers [279]. A study on 251 HBsAg-positive females (305 children, 176 born with assisted conception, and 129 born with natural conception; 7.5% of children were HBsAg positive at birth), found that HBsAg positivity rate among children at birth was similar in the assisted conception group and the natural conception group (6.3% vs. 9.3%) [280].…”
Section: Effect Of Female Chronic Hbv Infection On Pregnancy Outcomes...mentioning
confidence: 99%